BATAK TOBA MIGRANTS: ADAPTATION AND CULTURAL CHANGE IN THE CITY OF PEMATANGSIANTAR (MIGRAN BATAK TOBA: ADAPTASI DAN PERUBAHAN BUDAYA DI KOTA PEMATANGSIANTAR) - Corry Corry; Ulung Napitu; Togarman Damanik; Erick Sapetra Siburian (Universitas PGRI Sumatera Barat, 2022)
This research aims to be based on social changes experienced by Batak Toba migrants in Pematangsiantar City. The migrants did not adopt a particular ethnic culture but instead retained the socio-cultural values of batak-toba. However, Batak-Toba migrants did not become dominant in Pematangsiantar City, different in other areas that tended to be dominant. The method used to analyze data on the patterns of adaptation and socio-cultural changes of the Batak Toba people used descriptive qualitative methods. Through this method, it is hoped that it will be able to answer research problems. The population in this study is all Batak Toba migrants who live in Pematangsiantar City. Informants in this study as many as 12 people consisting of traditional Batak Toba figures as many as five people and as a comparison of simalungun indigenous figures one person, Angkola 1 person, Java 1 person, Malay 1 person, Minang 1 person, Karo 1 person, and China 1 person. Data is collected through in-depth interviews combined with library data. Interview results are collected, tabulated, analyzed, verified, and displayed until concluded. The results showed that the pattern of adaptation and socio-cultural changes experienced by Batak Toba migrants was influenced by the cultural background of Pematangsiantar City, namely Simalungun culture as the host culture and other cultures that were not dominant. Batak Toba migrants adapt in Pematangsiantar City to the local culture but retain most of its socio-cultural values, even if they become migrants and settle in Pematangsiantar City.